Analisis Strategi Pemerintah Desa Leppangeng Terhadap Partisipasi Masyarakat dalam Gotong Royong - Lego, Devianti; Adnah, A.Astinah; Hardianti; Razak, Muhammad Rais Rahmat; Lubis, Sandi (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the strategy of the Leppangeng Village government in increasing community participation in mutual cooperation activities, which has decreased due to the influence of modernization, personal busyness, education level, and the development of a culture of individualism. This research uses qualitative methods of data collection techniques through in-depth interviews, direct observation, and analysis using NVivo software. The results show that the strategies implemented by the government include routine socialization, deliberation with the community, direction, and the formation of community groups such as agricultural groups and family welfare empowerment. Although there is an increase in participation, community involvement tends to be temporary and uneven. Some of the inhibiting factors include busy work schedules, low education levels, gender roles, and limited understanding of the long-term benefits of mutual cooperation. The government has made efforts to evaluate and educate the community, but consistency of participation remains a challenge. Therefore, further strategies are needed in the form of strengthening communication, involving the community from the planning stage, providing incentives, and instilling the values of mutual cooperation as part of social identity. With a more comprehensive and sustainable strategy, it is hoped that the spirit of mutual cooperation dap will continue to grow.